Decoding the transmission and subsequent disability risks of rabineurodeficiency syndrome without recuperation - Yasir Ramzan; Bandar M. Fadhl; Shafiullah Niazai; Aziz Ullah Awan; Kamel Guedri (Scientific Reports)
Abstract This study presents a novel approach focused on extensively addressing the dynamics of Rabineurodeficiency Syndrome by developing a mathematical compartmental model without recuperation. The equilibria of the rabies-free and present states are analyzed locally and globally. Real-world data on annual rabies cases are integrated to confirm and enhance the model’s accuracy. Likewise, a parameter estimation technique is employed to optimize the model, aiding in calculating the basic reproduction number. Sensitivity analysis examines the impact of critical parameters on transmission dynamics, providing a deeper understanding of the determining factors influencing disease spread. Visual representations of the relationship between essential parameters and the reproduction number offer valuable insights into factors influencing disease control. Advancing the understanding of Rabineurodeficiency Syndrome dynamics, the inclusive control actions to mitigate infectious diseases are evaluated, emphasizing the importance of accounting for individuals with disabilities.